2020
DOI: 10.1007/s11525-020-09354-6
|View full text |Cite
|
Sign up to set email alerts
|

Competition between whole-word and decomposed representations of English prefixed words

Abstract: English aspiration is influenced by word structure: in general, a voiceless stop following s is unaspirated (des[t]royed), but it can be aspirated if a prefix-stem boundary intervenes (dis[tʰ]rusts) (Baker, Smith & Hawkins 2007). In a production study of 110 words prefixed with dis-or mis-, we show that even in prefixed words, there is variation (dis[k]laimers ~ dis[kʰ]laimers), and that aspiration in such words is correlated with word and stem frequency. The more frequent the word, the less likely aspiration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It is a frequency-based measure for morphological decomposability. Morphological decomposability, or segmentability, has been found to affect duration in a number of studies (Hay, 2003 , 2007 ; Pluymaekers et al, 2005b ; Schuppler et al, 2012 ; Zimmerer et al, 2014 ; Ben Hedia and Plag, 2017 ; Plag and Ben Hedia, 2018 ; Zuraw et al, 2020 ). The higher the relative frequency, the more decomposable the item is assumed to be.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a frequency-based measure for morphological decomposability. Morphological decomposability, or segmentability, has been found to affect duration in a number of studies (Hay, 2003 , 2007 ; Pluymaekers et al, 2005b ; Schuppler et al, 2012 ; Zimmerer et al, 2014 ; Ben Hedia and Plag, 2017 ; Plag and Ben Hedia, 2018 ; Zuraw et al, 2020 ). The higher the relative frequency, the more decomposable the item is assumed to be.…”
Section: Methodsmentioning
confidence: 99%
“…For derivation, too, studies have demonstrated effects of morphological structure on phonetic output. For example, morphological geminates in English differ in duration depending on morphological category and informativity (Ben Hedia and Plag, 2017 ; Ben Hedia, 2019 ), and phonetic reduction in various domains can depend on how easily speakers can decompose a complex word into its constituents (e.g., Hay, 2003 , 2007 ; Plag and Ben Hedia, 2018 ; Zuraw et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ranking of these factors is a matter we cannot address yet, nor do we have the numbers or methodologies that might clear up the picture (Elkins 2020; Zuraw et al 2021). Our findings nevertheless support a hypothesis that treats prefixes as the fifth column undermining the GSR from the earliest records on.…”
Section: Discussionmentioning
confidence: 99%
“…These two classes of models are not mutually exclusive (Wheeldon & Monsell, 1992;, and modern accounts often assume that the lexicon needs to include a combination of abstract representations and information about frequency of variants and morphological components (e.g. Hay & Baayen, 2005;Connine & Pinnow, 2006;Sciama & Dowker, 2007;Pierrehumbert, 2016;Zuraw et al, 2021). Even if normal lexical access does involve episodic representations, some sort of abstraction presumably needs to also be available, because compensation for phonological alternation occurs even in pseudowords -for example, in French, where obstruents can assimilate in voicing to a following obstruent, listeners not only interpret e.g.…”
Section: Introductionmentioning
confidence: 99%